Information Sharing and Information Quality in the Drugs and Medical Consumables Supply Chain Management (SCM): Drugs and Medical Consumables Supply Chain Management - Nouranian, Malikeh; Saghaeiannejad Isfahani, Sakineh; Memarzadeh, Hoda (Iranian Journal of Pharmaceutical Sciences, 2021)
Information management is considered as one of the keys to the supply chain management (SCM) success. This study intends to explore the factors affecting the knowledge sharing and knowledge quality in the SCM of the drugs and medical consumables. This applied study was conducted using analytical-survey research method. The research population consisted of 78 people involved in the supply chain of the drug and medical consumables in the teaching hospitals of Isfahan University of Medical Sciences (IUMS). Data were collected by a questionnaire whose face and content validity were both confirmed by pooling the ideas of some professors of Health Information Technology and Health-care Services Management faculties of IUMS. The reliability of the questionnaire was validated by estimating Cornbrash’s alpha coefficient (α=0.93). Data were analyzed using multiple regression analysis method and SPSS software version.23. Based on the results, the environmental uncertainty and intra-organizational facilitators had no impact on information sharing and information quality but inter-organizational relationships influenced the information sharing (p = 0.01) and information quality (p = 0.001). To achieve high-quality information sharing, establishing appropriate relationships with the other chain partners is of critical importance. Based on the results of the study, although there was no statistically significant relationship between the intra-organizational facilitators and environmental uncertainty and the information sharing and information quality, top management support, information technology (IT), appropriate selection of supplier and attention to the drug needs of the patients, should not be neglected.